Soreness and ulcers 3: due to vesiculobullous disease 2 - Nikitakis, Nikolaos (Henry Stewart Talks, 2017)
Diseases showing occasional subepithelial blister formation accompanied by basal cell destruction, Lichen planus, Lichenoid reactions, Contact stomatitis, Chronic ulcerative stomatitis, Lupus erythematosus, Diseases showing intraepithelial and/or subepithelial blister formation, Paraneoplastic pemphigus, Erythema multiforme